THE METHOD OF STRUCTURAL TRANSFORMATION OF STOCHASTIC NETWORKS FOR THE GERT-MODELING OF TECHNOLOGICAL AND ECONOMIC PROCESSES - Andryushchenko, V. O.; Skalozub, V. Vl. (Science and Transport Progress, 2008)
The method of structural transformation of graphs of stochastic networks is developed, which extends an application sphere of GERT-models for the analysis of casual economic and technological processes.